Implementation of stop smoking support by mental healthcare professionals: cross-sectional analysis of why nothing much happens - Eline Meijer (Discover Mental Health, 2025)
Abstract Smoking is highly prevalent and persistent among people with mental illness, but implementation of smoking cessation care by mental healthcare professionals (MHCPs) is lagging behind. This study took a broad approach to understanding implementation of stop smoking support (SSS) by MHCPs (N = 220 for main analyses), incorporating background characteristics, psychosocial factors, client factors, and organizational/environmental factors. Variable selection was based on previous work and the Consolidated Framework for Implementation Research. Cross-sectional survey data were collected online in the Netherlands from 2021 to 2022, and analyzed using logistic regression and regression tree analyses. Participants were 81 nurses, 74 psychologists, 40 psychiatrists, 12 child psychologists and 13 other MHCPs; aged 42 on average, 24% male, 14% currently smoked and 32% quit smoking. Results show that most MHCPs do not ask about smoking, do not advise or motivate clients to quit smoking, and do not refer clients motivated to quit to SSS. In order to improve this situation, proactive efforts should be undertaken to target MHCPs’ perceptions of clients’ responsibility and quit success, preferably through strategies that reach MHCPs regardless of their affinity with SSS, taking MHCPs’ profession and own smoking status into account.